Cloning of the promoter region of β-xylosidase (FaXyl1) gene and effect of plant growth regulators on the expression of FaXyl1 in strawberry fruit - Bustamante, Claudia Anabel (2009)
Expression and activity of cell wall modifying enzymes involved in fruit softening may be regulated by hormones and/or other signal molecules. In strawberry, FaXyl1 encodes for a fruit-specific b-xylosidase probably associated to hemicellulose degradation. In this work, we have isolated and analysed the promoter region of FaXyl1 gene. Analysis of the sequence revealed the presence of cis-acting elements associated with hormone, light and stress-related responses. Several treatments were done on fruit in order to prove the responsiveness of FaXyl1 to plant growth regulators related to the regulatory elements identified in the promoter region (abscisic acid, auxins and gibberellins) and others associated with the ripening process (ethylene and nitric oxide). The effect of each treatment on FaXyl1 expression, the corresponding protein levels and the b-xylosidase activity was evaluated. ABA (abscisic acid) stimulated FaXyl1 expression and protein levels. In contrast, expression levels of FaXyl1 gene decreased after treatments with NAA (naphthalene acetic acid), GA3 (gibberellic acid) and ethephon, an ethylenegenerating compound. SNP (sodium nitroprusside), a NO donor, did not affect FaXyl1 mRNA and protein levels. The effect of 1-MCP (1-methylcyclopropene), an ethylene perception inhibitor, on FaXyl1 expression was consistent with the effect observed with ethephon. b-xylosidase activity was down regulated by NAA, whereas GA3, ABA, ethephon, 1-MCP and SNP had no effect on it.